Low Expression of LDHB Correlates With Unfavorable Survival in Hepatocellular Carcinoma: Strobe-Compliant Article. Issue 39 (September 2015) - Chen, Ruohua; Zhou, Xiang; Yu, Zhenhai; Liu, Jianjun; Huang, Gang
Abstract : Abstract: Lactate dehydrogenase B (LDHB) is widely expressed in adult somatic tissue and plays important roles in the development of human cancers. However, the association between LDHB expression and the clinicopathological characteristics of hepatocellular carcinoma (HCC) is not well understood. The study was to detect the expression of LDHB in human HCC and investigate the association between its expression and the clinicopathological characteristics of HCC. Immunohistochemistry (IHC) analysis was performed to characterize the expression of LDHB in HCC and matched noncancerous tissues. Kaplan–Meier survival and Cox regression analyses were employed to evaluate the prognosis of 75 HCC patients. The results showed that the expression of LDHB in HCC was significantly lower than that in noncancerous tissues. Moreover, the expression level of the LDHB protein in HCC was correlated with pathological grade ( P = 0.037), vascular invasion ( P = 0.037), lymph node metastasis ( P = 0.016), and tumor-node metastasis (TNM) stage ( P = 0.007). Cox regression analysis further revealed that LDHB expression is an independent prognostic factor for disease-free survival ( P = 0.045) and overall survival ( P = 0.019). These data are the first to indicate that LDHB expression is a valuable prognostic biomarker for HCC and that low LDHB expression suggests unfavorable survival outcomes in HCC patients.